Correction: Different antitumor effects of quercetin, quercetin-3′-sulfate and quercetin-3-glucuronide in human breast cancer MCF-7 cells. Issue 7 (10th June 2019) - Wu, Qiu; Needs, Paul W.; Lu, Yalong; Kroon, Paul A.; Ren, Daoyuan; Yang, Xingbin
Abstract : Correction for 'Different antitumor effects of quercetin, quercetin-3′-sulfate and quercetin-3-glucuronide in human breast cancer MCF-7 cells' by Qiu Wu et al., Food Funct., 2018, 9, 1736–1746.